Literature Study: The Effect Of Guided Inquiry Learning Models On Physicslearning Outcomes Of Students - Nurmuhlisa (Science Education Doctoral Study Program, Postgraduate, Mataram University, 2025)
This study aims to examine the effect of guided inquiry learning models on students' physics learning outcomes through a literature review. The method used is a literature review by analyzing several journals and proceedings accessed through Google Scholar that are relevant to the topics of guided inquiry and physics learning outcomes. The results of the study show that the application of the guided inquiry learning model can improve students' physics learning outcomes, both in cognitive aspects and other supporting abilities such as learning activities, scientific attitudes, scientific communication, and critical thinking skills. This model provides opportunities for students to be directly involved in a guided investigation process, so that they are more active, focused, and able to build conceptual understanding independently with the guidance of a teacher. In addition, guided inquiry has been proven to be more effective than conventional learning in most studies, although one study showed no significant difference compared to independent inquiry. Overall, the guided inquiry learning model is an effective approach to improving the quality of physics learning